Pedagogi Digital Berbasis Kesesuaian Perkembangan Anak dalam Pendidikan Islam Anak Usia Dini: Systematic Literature Review - Sri Purwanti Nasution; Agus Suprijanto (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Digital transformation in early childhood education has created new opportunities and challenges for Islamic Early Childhood Education, particularly in ensuring that digital learning remains aligned with children’s developmental characteristics, Islamic values, and pedagogical ethics. This study aims to systematically review relevant literature on developmentally appropriate digital pedagogy in Islamic Early Childhood Education, with specific attention to teacher roles, child agency, parental involvement, and developmental risks. This research employed a Systematic Literature Review design guided by the PRISMA framework. Articles were identified through selected national and international scholarly databases using keywords related to digital pedagogy, early childhood education, Islamic early childhood education, developmentally appropriate practice, digital play, digital literacy, teacher mediation, and child well-being. The selected studies were analyzed using thematic synthesis to identify patterns, conceptual intersections, and research gaps. The findings indicate that digital pedagogy in Islamic Early Childhood Education should not be reduced to the technical use of digital tools; rather, it must be understood as an integrative pedagogical approach that combines developmentally appropriate practice, teacher mediation, child participation, parental guidance, digital safety, and the internalization of Islamic moral values. The review also reveals that excessive screen exposure, low-quality content, weak adult supervision, and passive digital consumption may pose risks to children’s holistic development. The novelty of this study lies in its integrative synthesis of digital pedagogy, child developmental appropriateness, and Islamic educational values. The study implies that Islamic early childhood institutions need clear pedagogical guidelines, digitally and religiously competent teachers, developmentally suitable Islamic digital content, and active parental collaboration to ensure safe, meaningful, and value-oriented digital learning for young children.